Zeolite‐Encaged Pd–Mn Nanocatalysts for CO2 Hydrogenation and Formic Acid Dehydrogenation. (15th September 2020) - Sun, Qiming; Chen, Benjamin W. J.; Wang, Ning; He, Qian; Chang, Albert; Yang, Chia‐Min; Asakura, Hiroyuki; Tanaka, Tsunehiro; Hülsey, Max J.; Wang, Chi‐Hwa; Yu, Jihong; Yan, Ning
Abstract: A CO2 ‐mediated hydrogen storage energy cycle is a promising way to implement a hydrogen economy, but the exploration of efficient catalysts to achieve this process remains challenging. Herein, sub‐nanometer Pd–Mn clusters were encaged within silicalite‐1 (S‐1) zeolites by a ligand‐protected method under direct hydrothermal conditions. The obtained zeolite‐encaged metallic nanocatalysts exhibited extraordinary catalytic activity and durability in both CO2 hydrogenation into formate and formic acid (FA) dehydrogenation back to CO2 and hydrogen. Thanks to the formation of ultrasmall metal clusters and the synergic effect of bimetallic components, the PdMn0.6 @S‐1 catalyst afforded a formate generation rate of 2151 molformate  molPd −1  h −1 at 353 K, and an initial turnover frequency of 6860 mol H 2  molPd −1  h −1 for CO‐free FA decomposition at 333 K without any additive. Both values represent the top levels among state‐of‐the‐art heterogeneous catalysts under similar conditions. This work demonstrates that zeolite‐encaged metallic catalysts hold great promise to realize CO2 ‐mediated hydrogen energy cycles in the future that feature fast charge and release kinetics. Abstract : Sub‐nanometer Pd–Mn clusters were encaged within silicalite‐1 zeolites by a ligand‐protected method under direct hydrothermal conditions. The obtained zeolite‐encaged metallic nanocatalysts exhibited a record formate generation rate of 2151 molformate  molPd −1  h −1 at 353 K, and an excellent initial turnover frequency of 6860 mol H 2  molPd −1  h −1 for CO‐free formic acid decomposition at 333 K without any additive.